MG-132 Diagnostic utility of whole genome sequencing in paediatric medicine. (4th December 2015) - Marshall, Christian R; Stavropoulos, Dimitri J; Jobling, Rebekah; Merico, Daniele; Bowdin, Sarah; Monfared, Nasim; Meyn, MStephen; Szego, Michael; Shaul, Randi Zlotnik; Thiruvahindrapuram, Bhooma; Pellecchia, Giovanna; Nalpathamkalam, Thomas; et al.
Abstract : Background: Chromosome microarray analysis (CMA) is the current first-tier clinical investigation for paediatric patients with congenital malformations and/or neurodevelopmental disorders. Whole genome sequencing (WGS) promises to capture all classes of genetic variation in a single experiment, but the diagnostic yield of WGS compared to CMA in the clinical setting has not been established. Objectives: The purpose of the study was to compare the diagnostic yield of WGS with CMA and other targeted sequence analysis. Methods: Through the SickKids genome clinic 100 consecutive patients undergoing CMA were recruited and WGS was performed to compare diagnostic yield. Results: WGS identified variants meeting clinical diagnostic criteria in 32% of cases, representing a 4-fold increase in diagnostic rate over CMA (8%) alone and > 2-fold increase in CMA plus targeted sequence testing (15%). WGS identified all reportable rare CNVs that were detected by CMA. In an additional 27 patients, WGS revealed clinically significant SNV and indel mutations presenting in a dominant (72%) or a recessive (28%) manner. Four cases had variants in at least two genes involved in distinct genetic disorders, contributing to a more complex clinical phenotype. Conclusions: Our data indicate that WGS is highly accurate and efficient, providing a diagnosis in 32% paediatric patients that meet clinical criteria for CMA. Clinical implementation of WGS as a single and primary molecular test will provide a higher diagnostic yield than conventional testing while decreasing the number of genetic tests and ultimately the time before reaching a genetic diagnosis.